Konsep Makna Ghurûr dalam al-Qur’an: Analisis Semantik Toshihiko Izutsu - Parhan Parhan; Ghufron Maksum; Ahmad Munir (Al Ashriyyah, 2022)
The ghurûr vocabulary in the Qur'an is a special word, but this privilege is something that must be avoided. Because the ghurur vocabulary in the Qur'an always has a negative purpose in every use. For this reason, in this study the author intends to examine the deeper meaning of the word. With the method of semantic analysis of the Qur'an developed by Toshihiko Izutsu, the resulting meaning is said to be relevant to the times. The stages that are passed in this Izutsu semantic analysis are finding the basic meaning and relational meaning, revealing the historical meaning, and finally describing the weltanschauung concept of the word ghurûr in the Qur'an. The findings obtained in this study are the fact that the concept of ghurûr formed in the Qur'an is a negative impression that must be avoided. Because the concept that is formed is a circle that is always under the control of the devil. Therefore, the recorded purpose of ghurûr is always connoted with a negative meaning.